Investigate Airport Service Quality- A Case Study of Airports in Shanghai - Jiang, Hongwei; Liang, Tianhui (International Journal of Business, Economics and Management, 2019)
Evaluating service quality is a critical task for airports aiming to identify aspects of airport service that contribute to differences in passenger satisfaction. The purpose of this paper is to investigate the airport service quality from passengers’ perspectives at two airports (Pudong and Hongqiao Airports) under the management of Shanghai Airport Authority (SAA) in China. Surveys at SAA have found that there are significant differences between passengers’ expectations and actual perceptions of service quality at SAA, which imply that SAA is advised to improve its service quality and reduce passenger dissatisfaction towards components comprising service quality as a whole. The components for which the largest gaps were found between expectation and actual perception were identified as “Shop and restaurant prices”, “Free Wi-Fi access”, “Play areas for children”, “Departure punctuality”, and “Various restaurants providing different kinds of food”. The results reveal that there are significant differences between gender, nationality and main travel purpose groups: women tend to assign significantly higher scores than men; domestic travellers reported high satisfaction than international ones; and passengers travelling for holiday and academic-related purposes reported higher satisfaction than those travelling for business. There is a positive correlation between airport service quality and passengers’ overall satisfaction at SAA. This paper aims to provide useful information for government officials in the identification of potential issues posed to passengers and that should be addressed by airport management.